Managerial overconfidence and corporate risk management - Tim R. Adam; Chitru S. Fernando; Evgenia Golubeva (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
We show that managerial overconfidence, which has been found to influence a number of corporate financial decisions, also affects corporate risk management. We find that managers increase their speculative activities using derivatives following speculative gains, while they do not reduce their speculative activities following speculative losses. This asymmetric response follows from selective selfattribution: successes tend to be attributed to one's own skill, while failures tend to be attributed to bad luck. Thus, our results show that managerial behavioral biases can also impact corporate risk management.
Keywords: G11; G14; G32; G39; 330; corporate risk management; behavioral biases; managerial overconfidence; speculation; Führungskräfte; Persönlichkeitspsychologie; Risikomanagement; Anlageverhalten; Bias; Spekulation; Schätzung; Goldbergbau; USA